Scanning electron microscopy leads to identification of novel nonedible oil seeds as energy crops. Issue 7 (5th April 2019) - Munir, Mamoona; Ahmad, Mushtaq; Waseem, Amir; Zafar, Muhammad; Saeed, Muhammad; Wakeel, Aneela; Nazish, Moona; Sultana, Shazia
Abstract: Currently, exploration of alternative energy resources is hotly debated among the scientific community owing to rising energy crises and environmental issues. Biodiesel, as renewable energy source proves to be a better option and substitute to petro diesel. In this regard, nonedible seeds could be a better feedstock for synthesizing biodiesel due to their cost effectiveness and environmental friendly attributes. The present study, therefore, deals with the exploration and identification of micromorphologic features among eight novel nonedible oil yielding seeds via scanning electron microscopy (SEM) as potential feedstock for biodiesel industry. Light microscopic studies revealed that seeds size vary from 0.1–2.9 cm in length to 0.1–3 cm in width. Moreover, a great variation in seed color from black, green, and different shades of brown was also observed. Seeds ultra‐structure examination by SEM exhibit great variation in seed shape, size, color, sculpturing and periclinal wall shape and arrangement and so on. All the understudy seeds vary from rounded, irregular, subspherical, ellipsoidal, reniform, flattened, polygonal, ovate, pyriform, oblong, and globose shape. Seeds wall structure exhibits great variation from entire, angular, straight, irregular, polygonal, smooth, and elongated. The periclinal wall pattern exhibits variation from flat to slightly concave‐convex with straight, angular, undulate, or dentate seeds margin. Among the studied species only Argemone ochroleuca Linn. (Papaveraceae) possess micropylar peak, ridged raphe, and basal helium. The obtained results from the present study would therefore, suggest that SEM could be a useful tool in refreshing the veiled micromorphological features among different oil yielding seeds which in turn helps the researchers for their correct identification, exploration, authentication, and seeds classification in future. Abstract : Research Highlights: Exploration of novel non‐edible oil yielding seeds as feedstock for biodiesel industry. Investigation of macro‐morphological (Size, shape and color) as well as micro‐morphological features (seed sculpturing, cell margins, periclinal wall shape and arrangement) among oil yielding seeds by utilization of latest techniques like Scanning electron microscopy (SEM) as additional tool in their identification. Evaluation of seeds oil content, free fatty acid content, biodiesel yield as well as fatty acid composition among understudy oil yielding seeds.